Features of blood microcirculation in the skin at children - O A Gurova (RUDN Journal of Medicine, 2011)
The characteristics of a skin blood microcirculation by method of laser Doppler flowmetry (LDF) in 70 children at the age from 4 till 7 years are studied. During this period of life, gradual decrease in intensity of blood microcirculation in the skin is observed. For surveyed children three types of microcirculation are characteristic: mesohaemic, hypohaemic and hiperhaemic. Mesohaemic type of microcirculation (51,4% of children) prevails with balanced sympathetic and parasympathetic regulatory influences.